2018
DOI: 10.1093/gbe/evy121
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Conservation and Diversification in the Fungal Polarization Network

Abstract: The combined actions of proteins in networks underlie all fundamental cellular functions. Deeper insights into the dynamics of network composition across species and their functional consequences are crucial to fully understand protein network evolution. Large-scale comparative studies with high phylogenetic resolution are now feasible through the recent rise in available genomic data sets of both model and nonmodel species. Here, we focus on the polarity network, which is universally essential for cell prolif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 99 publications
(132 reference statements)
0
33
0
Order By: Relevance
“…Polarized growth has been widely studied in S. cerevisiae , and a core of proteins have been identified (Arkowitz & Bassilana, ; Riquelme, ; Martin & Arkowitz, ; Diepeveen et al ., ). This core toolkit seems to be relatively well conserved across all fungal lineages, although no individual component appears to be completely essential (Diepeveen et al ., ). Within the kingdom, true hyphal growth is an evolutionary novelty of the ‘terrestrial fungi’, a monophyletic clade that includes the phyla Zoopagomycota, Mucoromycota, Glomeromycota, Ascomycota and Basidiomycota.…”
Section: Cellular Complexitymentioning
confidence: 97%
“…Polarized growth has been widely studied in S. cerevisiae , and a core of proteins have been identified (Arkowitz & Bassilana, ; Riquelme, ; Martin & Arkowitz, ; Diepeveen et al ., ). This core toolkit seems to be relatively well conserved across all fungal lineages, although no individual component appears to be completely essential (Diepeveen et al ., ). Within the kingdom, true hyphal growth is an evolutionary novelty of the ‘terrestrial fungi’, a monophyletic clade that includes the phyla Zoopagomycota, Mucoromycota, Glomeromycota, Ascomycota and Basidiomycota.…”
Section: Cellular Complexitymentioning
confidence: 97%
“…On the basis of this ancestral mechanism, Bem1 could then have evolved in a step-wise fashion. Given that Bem1 is highly conserved in fungi (Diepeveen et al, 2018), and that fission yeast polarization is based on the same mutual recruitment mechanism (Lamas et al, 2019;Martin and Arkowitz, 2014), this hypothetical evolutionary pathway would likely lie far in the past.…”
Section: How Evolution Might Leverage Scaffold Proteinsmentioning
confidence: 99%
“…Another possibility is to search for species in the current tree of life which contain intermediate steps of the evolutionary trajectory, for instance species with a more ancient version of Bem1 lacking the SH3 domain, and identify the protein self-organization principles underlying polarization in these species. This is becoming a more and more realistic option, given the very large (and still expanding) number of fungal species that has been sequenced (Diepeveen et al, 2018) and the growing interest of cell and molecular biologists to work with nonmodel systems (Russell et al, 2017).…”
Section: How Evolution Might Leverage Scaffold Proteinsmentioning
confidence: 99%
“…4A), where a Cdc42-based protein pattern on the cell membrane marks the site of bud emergence (Bi and Park, 2012). Cdc42 is a highly conserved membrane-bound small GTPase (Diepeveen et al, 2018) with two states: an active, GTP-bound, state, and an inactive, GDPbound, state. Switching between the two states is highly regulated and only Cdc42-GTP signaling towards the downstream processes is sufficient for bud formation.…”
Section: Polarity Establishment In Budding Yeastmentioning
confidence: 99%
“…How the functions of Bem1 are redistributed by removing the three other proteins remains to be discovered. How molecular functions are rearranged is also relevant beyond this specific experiment: comparative studies on 298 fungal strains and species showed that redistribution of functions over different proteins in the polarization network happens regularly over the fungal tree of life (Diepeveen et al, 2018), and theoretical work suggested that small changes in reaction rates or the topology of the polarization network can dramatically rearrange functions within the polarity network (Goryachev and Leda, 2017). A minimal system for pattern formation, where proteins can be selectively added and removed, might help the understanding of how molecular functions necessary for pattern formation can be redistributed during evolution.…”
Section: Towards a Minimal System For Pattern Formation In Budding Yeastmentioning
confidence: 99%